Antiferromagnetically coupled double perovskite as an efficient and robust catalyst for visible light driven water splitting at neutral pH. Issue 8 (11th February 2022) - Kumar, Nikhil; Rom, Tanmay; Mallick, Bidyut; Kaushik, Rahul; Ghosh, Amrita; Babu, P. D.; Panda, Swarup K.; Paul, Avijit Kumar
Abstract : CaLaScRuO6+ δ is a new disordered system acting as active photocatalyst for oxygen evolution reaction in presence of visible light. Theoretical study predicts the most stable magnetic orientation correlating the experimentally observed behavior. Abstract : Green and sustainable energy production through renewable sources is an enormously exciting field of research. Herein, we report an A-site lanthanum doped oxygen excess ruthenate (predominantly Ru 5+ -ions) double perovskite system, CaLaScRuO6+ δ (CLSR), as an excellent photocatalyst for water splitting. The well characterized polycrystalline compound shows canted antiferromagnetic (AFM) behavior due to the existence of disordered Ru-ions at the B-site. Based on density functional theory + U (Hubbard U ) calculations, we have estimated various magnetic exchange interactions and found that the ground state is antiferromagnetic in nature which is in perfect agreement with our experimental results. Detailed analysis of the electronic structure further reveals that the present system belongs to the family of charge transfer semiconductors with an energy gap of ∼0.45 eV. Finally, the material is found to proficiently work for the oxygen evolution reaction (OER) via visible-light driven water splitting at neutral pH in an ecofriendly manner.